La dinamica vodu in Benin: politica e pratica religiosa - Brivio, Alessandra (L'Uomo società tradizione sviluppo, 2022)
In the coastal area of Benin, the vodu is a widespread religious practice. In the last years, a vodu cult, called tron kpeto deka, has achieved an outstanding success. Its leaders and adepts define it a “modern” vodu, because it appears suitable to cope with the contemporary society dynamics: it is clean, tidy, its rituality is more simple, speedy and efficient. This vodu elaborates its own discourse of modernity that, in the local sense, speaks of desire of social progress and of confidence in a future of success and wellbeing. The history of tron kpeto deka started in Gold Coast, during the period of the anti witchcraft cults' widespread. During its geographical and historical path, that brought it from the Northern savannah region to the coastal area, the cult embedded signs, practices, symbols and objects evoking the universal religions and a vague and unpredictable idea of North. The post colonial Benin and the ambivalent relationship between politics and vodu, that was developed in that period, contributed to build a favourable ground for the tron kpeto deka. Its modernity and alien origins cope with the demands for a renewal of local religions: people who are no more comfortable with “archaic” vodu practices, who are more involved with contemporary dynamics and look at the universal religions as means to “enter the world”, seem to find in the tron kpeto deka a suitable religious alternative.